2013
DOI: 10.4269/ajtmh.12-0756
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Health Care Seeking for Diarrheal Illness in Young Children in Urban Slums of Kolkata, India

Abstract: Maternal practices regarding children's health care have been recognized as an important factor associated with mortality rates among children < 5 years of age. We focused on health care-seeking practices of primary caretakers of children < 5 years of age with diarrheal disease in Kolkata. We interviewed caretakers of 1,058 children in a baseline survey and 6,077 children on six subsequent surveys. The prevalence of diarrhea during the preceding 2 weeks was 7.9% in the baseline survey and 5.7% (lowest 3.5% to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…This is consistent with the most recent care-seeking estimates for Maharashtra, where similar proportions of facility-based care-seeking were observed by child sex for diarrhea, fever, and symptoms of ARI [5]. Similar care-seek-VIEWPOINTS RESEARCH THEME 2: IMPROVING COVERAGE MEASUREMENT ing by child sex has also been reported elsewhere in India [42]. While sex did not appear to be associated with the decision to seek care, this does not exclude potential bias at other stages of the management of childhood illness.…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with the most recent care-seeking estimates for Maharashtra, where similar proportions of facility-based care-seeking were observed by child sex for diarrhea, fever, and symptoms of ARI [5]. Similar care-seek-VIEWPOINTS RESEARCH THEME 2: IMPROVING COVERAGE MEASUREMENT ing by child sex has also been reported elsewhere in India [42]. While sex did not appear to be associated with the decision to seek care, this does not exclude potential bias at other stages of the management of childhood illness.…”
Section: Discussionsupporting
confidence: 88%
“…A study in Niger also revealed that one third of acute diarrheal under-five-year-old children were not taken to health facilities [31]. Another study, in Kolkata slums in India, reported that educated mothers/caregivers sought care at health facilities and home [32]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted have found the decision-making authority to be the father as well as the mother and the process of decision-making a complex one involving the elders as well. [9] Health-care seeking behavior is also largely influenced by various sociodemographic factors which affect the pattern and time taken to seek health care. Factors such as age, sex, family size, education, sanitation, and hygiene influence health-care seeking behavior.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Literature on health-care seeking behavior of parents regarding child health problems and factors affecting it, in an urban slum setting in India is scarce. [9] Hence, our aim is to study the health-care seeking behavior of parents, especially in the urban setting as it is a resource limited and underserved group. Hence, a thorough understanding of health-care seeking behavior is of utmost importance in planning and formulation of interventions for controlling and decreasing child morbidities in a developing country like India.…”
Section: Introductionmentioning
confidence: 99%